The Internet Squash Federation
The only internet homepage sanctioned by the World Squash Federation. Contents: - Equipment (Rackets, Courts, Clothing ...) - Rankings ( World Men, World Women ...) - Rules of Squash (Singles Game, Doubles Game ...) - Countries & Regional Federations ( Africa, Asia, Europe, Oceania, Panamerica ...) - World Squash Federation ( About, History ...) - Media ( Books, Videos, Talk ...) - Clubs (Coaching, Holidays ...)